NEW 6-(3-INDOLYL)BENZO[B]CARBAZOLES - Mardi Santoso (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2001)
Some attempts have been carried out to synthesize polycyclic heterocyclic compounds derived from new benzocarbazoles (1). New 6-(3-indolyl)benzo[b]-carbazoles (2a) have been synthesised in good yields from the reaction of simple indoles and o-phthaldialdehid in methanol catalysed by p-toulenesulfonic acid monohydrate. Their precise structure were established by microanalysis, spectroscopy, and X-ray crystallography of the benzo[b]carbazole (2a).Keywords: indoles, polycyclic heterocyclic compounds, benzo[b]carbazoles